FOOD: INVISIBLE BRIDGE CONNECTING THE PAST AND PRESENT DAY OF DIASPORIC IDENTITY - Sri Hariyatmi (University of Muhammadiyah Malang, 2019)
As people migrate, they move along with their emotional luggage including flavors, aromas, smells, and their gastronomical experience that also travel with them. This paper seeks to explore the role of food in the life of diaspora and how their negotiation to choose food in their new “home” has become a magical space that allows them to reconfigure their sensory system and eventually makes them a person with richer sensory systems. Several studies have been conducted to explore the relationship between personal identity and food preference. None, however, discusses how food choice influences the reconstruction of identity. Thus, this study aimed at filling the niche by exploring the relationship between food and its influence in reconstructing identity quest. This qualitative study collected its data from ten diasporas living in Thailand and Indonesia by using an informal semi-structured interview. The interview results were employed as the main data of this study. In addition, a descriptive qualitative technique was used to analyze the data. Drawing on Babha’s concept of hybridity, this paper argues that firstly, food is an invisible bridge connecting the past and present-day of diasporic identity. Secondly, it also served as the shrine of negotiation for the diaspora in this study to reconfigure their identity in enduring adversity from living under a new dominant culture.